Upaya Meningkatkan Motivasi Belajar Matematika Melalui Penggunaan Media Kartu Angka pada Siswa Kelas III SDN 213/II Lubuk Beringin - Asad, Muhammad (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the mathematics learning motivation of third-grade students at SDN 213/II Lubuk Beringin through the use of number card media. This research is a Classroom Action Research (CAR) conducted in two cycles. "The subjects of this study were 11 third-grade students. The instruments used in this study were observation sheets, motivation questionnaires, and documentation. The collected data was analyzed using a qualitative and quantitative descriptive approach. The results showed an increase in students' learning motivation after the implementation of number card media, in terms of activeness, enthusiasm, and engagement during the learning process. Therefore, the use of number card media can be considered an effective alternative to enhance students' learning motivation in lower grade elementary school mathematics.